MONITORING OF ACRIDOIDS OF SEMIDESERTIC ZONE OF WEST KAZAKHSTAN REGION - Gabdulov, M.A.; Zhanatalapov, N.Zh.; Makanova, G.N. (Западно-Казахстанский аграрно-технический университет имени Жангир хана, 2015)
About 270 types of acridoids insects live in various natural-economic zones of Kazakhstan. The greatest danger to agricultural lands is constituted by 15-20 types. Especially dangerous types among them are: Asian, locust (Locusta migratoria) and Italian locust (Calliptamus italicus) on the extent of distribution and level of injuriousness. As a result of our researches, the data were obtained on structure of acridoids fauna, biological efficiency of modern insecticides in conditions of semidesertic zone of West Kazakhstan region.
Keywords: Fodder lands; acridoids; Asian locust; Italian locust; monitoring; egg-pods; insecticides; biological efficiency